Climate change and the provision of biodiversity in public temperate forests – A mechanism design approach for the implementation of biodiversity conservation policies. (15th September 2019) - Augustynczik, Andrey Lessa Derci; Yousefpour, Rasoul; Hanewinkel, Marc
Abstract: The provision of forest biodiversity remains a major challenge in the management of forest resources. Biodiversity is mostly considered a public good and the fact that societal benefits from biodiversity are private information, hinders its supply at adequate levels. Here we investigate how the government, as a forest owner, may increase the biodiversity supply in publicly-owned forests. We employ a mechanism design approach to find the biodiversity provision choices, which take into account agents' strategic behavior and values towards biodiversity. We applied our framework to a forest landscape in Southwestern Germany, using forest birds as biodiversity indicators and evaluating the impacts of climate change on forest dynamics and on the costs of biodiversity provision. Our results show that climate change has important implications to the opportunity cost of biodiversity and the provision levels (ranging from 10 to 12.5% increase of the bird indicator abundance). In general, biodiversity valuations needed to surpass the opportunity cost by more than 18% to cope with the private information held by the agents. Moreover, higher costs under more intense climate change (e.g. Representative Concentration Pathway 8.5) reduced the attainable bird abundance increase from 12.5 to 10%. We conclude that mechanism design may provide key information for planning conservation policies and identify conditions for a successful implementation of biodiversity-oriented forest management. Graphical abstract: Image 1 Highlights: We investigate the provision of biodiversity in publicly owned forests. Climate change and willingness-to-pay are determinant for the optimal supply. Mechanism design can support a successful implementation of conservation policies.